Two species of Cleonini new for Pakistan and new synonymies Coleoptera: Curculionidae: Lixinae) - Ahmed, Zubair; Meregalli, Massimo; Fatima, Nadia (Zootaxa, 2016)
The superfamily Curculionoidea contains over 60,000 described species worldwide (Oberprieler et al. 2007). Knowledge of their distribution is still incomplete, with particular regard for several poorly or not yet completely investigated countries. Moreover, a large number of unidentified specimens of various geographical origin are conserved in museums throughout the world, and further unpublished data for many species can be recovered from the study of public and private collections.